2021
DOI: 10.1002/jcp.30419
|View full text |Cite
|
Sign up to set email alerts
|

Active autophagy in cancer‐associated fibroblasts: Recent advances in understanding the novel mechanism of tumor progression and therapeutic response

Abstract: Autophagy is primarily a homeostatic and catabolic process that is increasingly being recognized to have a pivotal role in the initiation and maintenance of cancer cells, as well as in the emergence of therapeutic resistance. Moreover, in the tumor microenvironment (TME) autophagy plays a crucial and sometimes dichotomous role in tumor progression.Recent studies show that during the early stages of tumor initiation, autophagy suppresses tumorigenesis. However, in the advanced stage of tumorigenesis, autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 156 publications
(154 reference statements)
0
8
0
Order By: Relevance
“…Then, in response to changes in the TME, these CAFs secrete pyruvate and lactate that can be used by epithelial cancerous cells to generate energy and enhance their proliferative capacity via oxidative phosphorylation (OXPHOS) [140]. The metabolism of tumor cells is also influenced by CAFs-modulated autophagy and oxidative stress pathway to promote tumor cell proliferation and drug resistance [141][142][143][144][145].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Then, in response to changes in the TME, these CAFs secrete pyruvate and lactate that can be used by epithelial cancerous cells to generate energy and enhance their proliferative capacity via oxidative phosphorylation (OXPHOS) [140]. The metabolism of tumor cells is also influenced by CAFs-modulated autophagy and oxidative stress pathway to promote tumor cell proliferation and drug resistance [141][142][143][144][145].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Autophagy has different effects on tumors under different circumstances . On the one hand, basal autophagy is considered an important factor in inhibiting cancer development, and its ability to remove damaged mitochondria can reduce reactive oxygen species production and thus inhibit tumor generation and progression. , but on the other, autophagy can provide the required energy for tumor cells and further promote tumor development . Therefore, regulation of autophagy can be an effective strategy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TMB and TIME were identified as important determinants of the efficacy of ICIs and in the prognosis of cancer patients ( Wu et al, 2021b ). Moreover, Jena et al (2021) have demonstrated that autophagy was closely related to TIME and participated in tumor progression. To explore the relationship between the ARlncRNA signature and tumor immunity thoroughly, we conducted ssGSEA to investigate the immune status in different groups.…”
Section: Discussionmentioning
confidence: 99%